The Influence Of Competence, Due Professional Care, Integrity, And Auditor Independence On Audit Quality With The Implementation Of Quality Assurance As A Moderating Variable: Study On The Audit Unit Of The East Java DJBC Regional Office I - Perdana, Taufan Aditya; Wahidahwati; Priyadi, Maswar Patuh (Neo Journal of economy and social humanities, 2023)
This study aims to test and analyze the effect of competence, due professional care, integrity, and auditor independence on audit quality with the implementation of quality assurance as a moderating variable. The study population was functional auditors and executors of examiners assigned to assist in conducting audits at the Regional Office of the Directorate General of Customs and Excise East Java I. The sampling technique used a saturated sample, namely the entire population totaling 47 (forty-seven). The sampling technique used saturated samples, namely the entire population of 47 (forty-seven) people as research samples. This type of research is quantitative research, with data collection methods through questionnaires. The data analysis technique to test the hypothesis uses Partial Least Square - Structural Equation Modeling with the SmartPLS program.The results showed: 1) auditor competence has a significant and positive effect on audit quality, 2) due professional care has a significant and positive effect on audit quality, 3) auditor integrity has a significant and positive effect on audit quality, 4) auditor independence has no effect on audit quality, 5) implementation of quality assurance has a significant and positive effect on audit quality, 6) the implementation of quality assurance is able to moderate the effect of auditor competence on audit quality, 7) the implementation of quality assurance is able to moderate the effect of due professional care on audit quality, 8) the implementation of quality assurance does not moderate the effect of auditor integrity on audit quality, 9) the implementation of quality assurance does not moderate the effect of auditor independence on audit quality.